2015
DOI: 10.1134/s1063773715070026
|View full text |Cite
|
Sign up to set email alerts
|

Parametric modulation of dynamo waves

Abstract: Long-term variations of solar activity, including the Grand minima, are believed to result from temporal variations of dynamo parameters. The simplest approximation of dynamo waves is applied to show that cyclic variations of the parameters can lead to an exponential growth or decay of magnetic oscillations depending on the variations frequency. There is no parametric resonance in a dynamo, however: the selective sensitivity to distinct frequencies, characteristic of resonant phenomena, is absent. A qualitativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This nonresonant parametric amplification can also be of importance for long-term variations of magnetic activity as, for example, found in the solar dynamo models of Ref. [40].…”
Section: Discussionmentioning
confidence: 72%
“…This nonresonant parametric amplification can also be of importance for long-term variations of magnetic activity as, for example, found in the solar dynamo models of Ref. [40].…”
Section: Discussionmentioning
confidence: 72%
“…We found that the consideration of a low-amplitude stochastic 'magnetic noise' as an additional poloidal source in the Babcock-Leighton model recovers the solar cycle every time the cycle is kicked into a grand minimum and reasonably mimics the occurrence statistics of the grand minima inferred from the cosmogenic radionuclides. It also exhibits bimodal distribution of toroidal magnetic energy (a proxy of sunspot number) implying the presence of two distinct modes of activity (Kitchatinov & Nepomnyashchikh 2015) and reproduces the phase space collapse, which is a signature of the only directly observed grand minimum, i.e. the Maunder minimum.…”
Section: Discussionmentioning
confidence: 77%
“…In other words, the grand minima cannot be considered as events that correspond to a tail of a single regular mode of solar activity. This bimodal nature in the probability density of smoothed SSN is actually due to the hysteresis present in the model (Kitchatinov & Nepomnyashchikh 2015). It should be noted that the hysteresis is a phenomenon where bistable solutions exist in a certain parameter regime and either of them is realized depending upon the system's initial conditions.…”
Section: 'Magnetic Noise' As a Possible Mechanism For The Recovery Fr...mentioning
confidence: 91%
“…Thus this dependence of the magnetic field with the dynamo number exhibits a hysteresis behavior. Further, in a simplified model, Kitchatinov & Nepomnyashchikh (2015) demonstrated that transitions 266-2 V. Vashishth et al: Subcritical Dynamo and Hysteresis in a Babcock-Leighton Type Kinematic Dynamo Model between two modes (subcritical dynamo with finite magnetic field and supercritical dynamo) qualitatively reproduce two distinct modes in the distribution of solar activity as inferred from cosmogenic isotope content in natural archives (Usoskin et al 2014). This behavior was further supported by Karak et al (2015) in the turbulent dynamo simulations.…”
Section: Introductionmentioning
confidence: 65%